Demographic Variables and Their Impact on Job Satisfaction Levels Among Employees of Government Units in the Sultanate of Oman - Al-Ubaidani, Amira Hamed Said; Ouazzani, Zineb Touhami (Journal of Economic, Administrative and Legal Sciences, 2025)
The importance of the study lies in enriching the scientific literature related to the relationship between demographic variables and job satisfaction levels. The results of the study could contribute to improving administrative policies within these units. The problem of the study lies in the clear disparity in the results of previous studies related to job satisfaction, where some studies showed high levels, others low, and some moderate. The current study aimed to identify the level of job satisfaction among employees of government units in the Sultanate of Oman and the impact of demographic variables on job satisfaction levels. The study relied on the descriptive survey method, which aims to accurately describe the phenomenon under study by collecting data using a questionnaire and then analyzing it to reach generalizable results. The method is characterized by integrating both quantitative and qualitative data to provide comprehensive and accurate information about the problem under study. A well-known and established instrument in the field of job satisfaction, namely the "Job Satisfaction Survey" (JSS) developed by Spector (1985), was used as the primary data collection tool. This survey includes 36 items designed to measure nine facets of the job and work environment (salary, promotion, supervision, benefits, contingent rewards, operating procedures, coworkers, nature of work, and communication). A total of 484 questionnaires were distributed using stratified random sampling to the study sample across various administrative divisions within the 37 government units. The data were analyzed using the Statistical Package for Social Sciences (SPSS). The study results indicated that the level of job satisfaction among employees of government units in the Sultanate of Oman was moderate, with a mean score of 3.17 and a standard deviation of 0.38. Additionally, the results showed no statistically significant differences between the following demographic variables (gender, age, educational qualification, job position, and years of service) and job satisfaction levels.
Keywords: job satisfaction; demographic variables; government units